Влияние граничных условий на активное демпфирование колебаний пластины при использовании показателей сенсоров - Карнаухова, Т.В. (Прикладная механика, 2010)
Basing on new approach, an effect of boundary conditions on effectiveness of active damping of forced resonance vibrations of a viscoelastic orthotropic plate is studied. The cases of hinged and rigid fixing the plate ends as well as the case of mixed boundary conditions are considered. The problems are solving by the Bubnov – Galerkin method. For each of mentioned cases, the formulas for potential differences are obtained, which should be applied to the actuator for damping the first mode of vibrations. It is shown that boundary conditions, dissipative properties of the material and size of sensor and actuator effect essentially on effectiveness of active damping of the plate vibrations.